Adams’ theory of goodness as Godlikeness amended - Kazemi, Seyyed Abbas (International journal for philosophy of religion, 2023)
In his Finite and Infinite Goods, Robert Adams puts forward a theistic framework for ethics according to which finite objects of value become good through resembling God who is the infinite Good and is the source and criterion of goodness. One question that immediately arises regarding this theory is whether any resemblance to God is sufficient for goodness or not. Adams’ answer to this question is negative. He puts forward further qualifications that resemblances to God have to meet so that they can constitute goodness in finite objects of value. In his God and Moral Law, Mark Murphy objects to these qualifications as inadequate for addressing the sufficiency question and puts forward his own suggestion as to how Adams’ theory has to be amended. In this paper I will first argue that Murphy’s suggestion for fixing the goodness as Godlikeness thesis is not an alternative to Adams’ proposed qualifications on resemblances to God and is best understood as an insightful interpretation and elaboration of Adams’ proposed qualifications. I will then show that as it stands, Murphy’s suggestion is not up to this task and itself is in need of reconstruction. Drawing on Judith Thomson’s discussions of goodness and virtue in her book Normativity, I will try to reconstruct Murphy’s suggestion and come up with an interpretation of Adams’ goodness as Godlikeness thesis that is more elaborate, informative, and plausible than Adams’ original formulation.